Análisis comparativo entre los sistemas de educación superior de Ecuador y Bolivia - Macias, Martha Concepción (2017)
This is a comparative analysis of higher education systems in Ecuador and Bolivia, countries that are characterized by cultural diversity and geographic proximity; its evolution in the higher education system has progressed in recent years with different rate. Reason given, the aim of this work is to make a comparison, to understand the similarities and differences between the systems of higher education in Ecuador and Bolivia, and thus, we can have a diagnosis in relation to the structure of the higher education system of both countries. In this context, we provide an overview about the situation or reality in which both institutions of Higher Education (IES) are developed. Also, the aspects that distinguish the higher education in these countries such as their regulations are mentioned, their internal political contexts, resources, segments, management, technological evolution; and the change of the political, economic and social model. In this way, a description of the main features of the Ecuadorian and Bolivian higher education systems is made, which is summarized in a comparative chart showing the similarities and differences that characterizes them